KESIAPSIAGAAN MASYARAKAT DESA SARAMPAD PASCA GEMPA CIANJUR: ANALISIS DAN STRATEGI PENINGKATAN - Rizkia, Saska Shafira; Endasmoro, Titan Kesuma; Jannah, Mutia Raudatul (STKIP PGRI Situbondo, 2025)
The earthquake that occurred in Cianjur Regency on November 21, 2022, caused severe damage, especially in Sarampad Village, Cugenang District. There is a red zone in Sarampad Village with an area of ±27.70 Ha, and it is located in a residential area. The number of casualties was caused by the epicenter being close to residential areas. This study was conducted to determine the preparedness index value of the community living in Sarampad Village in facing an earthquake disaster and identify the most influential parameters using multiple linear regression methods. Data was collected by completing questionnaires to community representatives in the scope of neighborhood associations (RT) and neighborhood associations (RW). The parameters used to calculate the community preparedness index are knowledge, early warning system, emergency response plan, and resource mobilization. The results of this study show that the Sarampad Village Community Preparedness Index is 0.31, including in the low category, with the most influential parameter being Resource Mobilization. This study highlights the importance of improving preparedness through strengthening early warning systems, disaster education, optimizing emergency response plans, and developing more systematic resource mobilization strategies to mitigate future disaster risks.